(untitled) (Global Journal of Human-Social Science, 2013)
The notion of human wellbeing itself is more broadly conceived to include not only consumption of goods and services but also the accessibility of all sections of the population especially the deprived and those who are living below the normative minimal poverty line to the basic necessities of a productive and socially meaningful life Analysis of data from the World Values Surveys demonstrates that the linkage between individual resources emancipative values and freedom rights is universal in its presence across nations regions and cultural zones A specific focus on these aspects of development is necessary as experience shows that economic prosperity measured in terms of per capita income It does not always ensure enrichment in quality of life reflected in broader dimensions of well-being like in indicators on longevity literacy or for that matter environmental sustainability Attainments in these dimensions of welfare are desirable in themselves hence they are socially valued This study demonstrates that socio-economic development emancipative cultural change and democratization constitute a coherent syndrome of social progress a syndrome whose common focus has not been properly specified by classical modernization theory